Developing LKPD using the STEAM approach to facilitate the creative mathematical thinking ability of grade X students - Safitri, Widiana; Yuanita, Putri; Suanto, Elfis (Jurnal Gantang, 2025)
This study is based on the observation that students struggle to think mathematically creatively when studying statistical material, and that there is currently no effective learning tool to help students develop this skill. The purpose of this research is to inform the creation of a STEAM-based statistics worksheet for use with students in class X SMA/MA, to foster their capacity for mathematical creativity. This research uses the 4D model, including Define, Design, Develop, and Disseminate. Data collection techniques included observations and interviews. This study involved students from Class X at SMAN 2 Siak Hulu. The results indicate that LKPD is valid, based on expert review, and practical, as demonstrated by the field test. At the field trial stage, the LKPD developed meets the assessment aspects: ease of use, presentation, readability, and time. So, the STEAM-based LKPD can be used during learning to facilitate creative mathematical thinking abilities.